It is not enough to show, it has to sell: (dis)agreements between fashion and market - D’Almeida, Tarcisio (2008)
The essence of consumption has been translated into fashion since it was created in Renascence until modern times in the XIX and XX Centuries and early in the XXI Century. In fashion world, creativity attains a merchandizing feature both in symbolic-aesthetic and economical-financial dimension and it could not exist without an equation that counterbalances the freedom of creativeness possessed by the high fashion and prêt-à-porter stylists – the arbitrators for concepts/tendencies “suggestions” to the society. This suggestion, in turn, impels the fashion creators to fit themselves to their target. How far could a fashion tendency survive regardless themarket rules? This article outlines some insights about this issue.